PENGARUH PEMBERIAN BERBAGAI JENIS PUPUK KANDANG TERHADAP PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L. - NUR ALAMSYAH, MUHAMAD; SABARUDDIN, LAODE; NURMAS, ANDI; WIJAYANTO, TEGUH; ARSYAD, MIRZA ARSIATY; SAFUAN, LA ODE (Jurnal Agroteknos, 2023)
This study aims to determine the effect of the application of various types of manure on the production of mung bean. The research was carried out at the Field Laboratory of Experimental Gardens II, Faculty of Agriculture, Halu Oleo University, Kendari, from October to December 2021. The study used a randomized block design consisting of four treatments, namely control (P0), cow manure 10 t ha-1 (P1), goat manure 10 t ha-1 (P2) and chicken manure 10 t ha-1 (P3). Each treatment was repeated 4 times so that there were 16 experimental units. Variables observed were number of pods, pod weight, seed weight, weight of 100 seeds, seed production ton ha-1, analyzed by variance. If the variance shows a significant effect, then proceed with the Least Significant Difference Test (BNT) at the 95% confidence level. The results showed that the application of manure can increase the production of mung bean plants. Treatment of chicken manure 10 t ha-1 (P3) gave a better effect on the number of pods, pod weight, seed weight and seed production t ha-1.